2013
DOI: 10.1038/emm.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

Brain site-specific proteome changes in aging-related dementia

Abstract: This study is aimed at gaining insights into the brain site-specific proteomic senescence signature while comparing physiologically aged brains with aging-related dementia brains (for example, Alzheimer's disease (AD)). Our study of proteomic differences within the hippocampus (Hp), parietal cortex (pCx) and cerebellum (Cb) could provide conceptual insights into the molecular mechanisms involved in aging-related neurodegeneration. Using an isobaric tag for relative and absolute quantitation (iTRAQ)-based two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 120 publications
(156 reference statements)
12
77
4
Order By: Relevance
“…This theory is further supported by previous results that indicated proteasome activity impairment in AD-related neurodegeneration [266,267,[341][342][343][344]. Furthermore, a human in vivo study that used the metabolic marker 13 C 6 -leucine to trace the production and clearance rates of Aβ 40 and Aβ 42 in the CSF indicated that Aβ was produced at the same rate in both the AD (which ranged from very mild to mild AD) and control groups; however, the Aβ clearance in the AD group was significantly (~35 %) lower than the control group.…”
Section: Chaperones and Co-chaperones In Adsupporting
confidence: 73%
See 1 more Smart Citation
“…This theory is further supported by previous results that indicated proteasome activity impairment in AD-related neurodegeneration [266,267,[341][342][343][344]. Furthermore, a human in vivo study that used the metabolic marker 13 C 6 -leucine to trace the production and clearance rates of Aβ 40 and Aβ 42 in the CSF indicated that Aβ was produced at the same rate in both the AD (which ranged from very mild to mild AD) and control groups; however, the Aβ clearance in the AD group was significantly (~35 %) lower than the control group.…”
Section: Chaperones and Co-chaperones In Adsupporting
confidence: 73%
“…In addition, other pivotal proteins of the chaperone/ proteasomal pathways, such as heat shock proteins (HSPs), FK506-binding proteins (FKBPs), and tripartite motif (TRIM) family proteins, were also altered in AD [118,267].…”
Section: Transmission Of Aβ and Taumentioning
confidence: 98%
“…With the advent of quantitative proteomics using ICAT (65), iTRAQ (66), AQUA (67), SILAC (68), SILAM (69), and label-free quantification approaches (70) some of these issues have been resolved and differential proteomic profiling in combination with absolute and relative quantifications can address changes of the neuronal proteome associated with diseases (e.g. [71][72][73][74][75][76][77][78][79] or is able to tackle protein half-lives (80,81). Crucial to all of these approaches are absolute high fidelity in the technical prerequisites of the analyses including accuracy of workflows, validity of data, dynamic range of protein assessment, or PTM levels.…”
Section: Figmentioning
confidence: 99%
“…Among their findings is a FUS-regulated alternative splicing of XPR1, which causes the elongation of Exon 13 on motor and cortical neurons. Manavalan et al (2013) analyzed proteome changes in brain linked to aging-related dementia. XPR1 molecule was included in the hippocampus network along with other 34 proteins whose expression is modulated in the hippocampus in AD brains.…”
mentioning
confidence: 99%